(untitled) (Research, Society and Development, 2023)
Society is in a process of constant transformation and, likewise, the challenges presented to young people. It cannot be denied that different factors have been causing changes in the way families function, however, values such as the importance of relationships are still highlighted as irreplaceable. Thus, the question raised by this article aims to identify some of the challenges faced by families, especially related to communication between parents and adolescent children. Could it be that today’s teenagers are very different from those of previous generations, especially in relation to the communication established with their parents? By seeking to outline the obstacles identified in this process, it is possible to provide a more reflective look at the current relationships established between the different generations in the family. This is a qualitative bibliographical review research that used the focus group investigation method as an instrument for data collection, a technique derived from group interviews, which collects information through interactions. Six teenagers between the ages of 15 and 17 participated in the research. The interviews were transcribed and analyzed using the Laurence Bardin content method. The results pointed to the importance of communication established between parents and children in strengthening affective bonds, emphasizing factors that hinder or facilitate communication, such as the need for adolescents to perceive a greater openness on the part of parents to listen to and understand them in your demands.